An image encryption algorithm based on XOR operation with approximation component in wavelet transform - Singh P.K.; Singh R.S.; Rai K.N. (My University, 2025)
Wavelet transform of the image generates the different components basically classified in the approximation and detail components. The approximation component has major information. In this paper a partial encryption technique is used, using only approximation component. In this paper a random array is generated which is XORed with the approximation component. The inverse transform of the matrix generated by this operation generates the encrypted image. The random array, the wavelet used and level of wavelet transform jointly serves as the key for the decryption process. In decryption is just reverse of the encryption steps. © 2015 IEEE.